Tissue Culture of 40 Year Old Clump of Bambusa Nutans Munro Culture - Sharma, S. K.; Kalia, Sanjay (Indian Forester, 2012)
Nodal segments taken from 40 yr old clump were surface sterilized using 0.1% (w/v) HgCl2 solution for 15-20 minutes and placed aseptically on media supplemented with 7.5µM BAP for bud break (79.16 ± 7.22) and it was observed within a period of two weeks. Sprouted shoots were excised along with small piece of mother tissue and kept on medium supplemented with 5.0µM BAP for multiplication for 4-5 subculture cycles. Bunch of three shoots exhibited faster shoot multiplication when cultured on multiplication media. During multiplication phase, BAP alone proved to be superior to kinetin. Microshoots exhibited higher rooting percentages on media supplemented with IBA than other auxins (IAA or NAA). Effective IBA concentration was found to be 10µM on which 72.22% of propagules rooted. Hardening was effectively carried out on half strength MS media without growth regulators, vitamins and sucrose. Success was achieved in acclimatizing 73.33% rooted propagules on mixture carrying potting mix of sand:FYM: Soil in l:l:l in poly-tunnels. Acclimatized plantlets were successfully transplanted to pots.